Spirituality of unity in management - Economy of Communion - Stanisław Grochmal (Cogent Business & Management, 2016)
The spirituality of unity in management processes is presented in the paper. The idea of the Economy of Communion (EoC) project and its realization in more than 800 businesses worldwide as an example of the striving for the eradication of poverty and new style of management is analysed. As an implementation of spirituality in management process, a new paradigm of unity in management sciences is proposed. On the basis of analysis of literature and discussions with experts and entrepreneurs of EoC businesses, six content dimensions of the paradigm of unity are formulated and the empirical research on the evaluation of these dimensions by testing the entrepreneurs of 110 businesses from 22 countries as well the management experts is considered. This research allowed verifying the hypothesis that the paradigm of unity shapes a new organizational culture by the creation of a suitable organizational climate in the EoC businesses.